Secure land rights incentivize community-led rangeland restoration, Kiteto District, Tanzania - Olesikilal, Birikaa; Spinelli, Madison (2024)
Spanning four villages- Amei, Lolera, Lembapuli and Lesoit- and covering an expansive 81,237 hectares, the ALLOLE shared grazing land cluster stands as the largest in Kiteto District, Tanzania. This cluster serves as one of four sites in Tanzania for the CGIAR Research Initiative on Livestock and Climate participatory rangeland management (PRM) innovation, aiming to enhance the capacities of communities in managing, governing, securing and restoring their lands. In collaboration with ILRI, KINNAPA Development Programme, Tanzania Ministry of Livestock and Fisheries, National Ranching Company (NARCO), Tanzania Livestock Research Institute (TALIRI), PRM actively supported bush thinning, covering 112.785 hectares in the cluster.